The impact of E-education and innovation on unemployment reduction among graduates: A way forward for higher educational institutes - Mian, Lu; Hussin, Ridzuan; Slaninová, Mgr. Gabriela; Shahzadi, Yusra (Frontiers in Psychology, 2022)
Recently the use of digital skills as a tool to alleviate unemployment concerns of University graduates has gained considerable attention among Governments in the developing economies. The present study examines the impact of E-education program (a digital initiative to train university graduates to get self-employed) on the unemployment reduction of young graduates of Higher Educational Institutes (HEI’s). We also explore the mediating influence of innovation in the association between E-education and unemployment reduction. The target population of the study were the students who have successfully completed the E-education courses. The convenient sampling technique was used for data collection from 416 respondents through a structured questionnaire. Collected data was analyzed using different statistical techniques like descriptive statistics (reliability analysis, normality analysis & correlation) and Structural Equation Modeling (SEM) for measurement of the structural model. The study findings assert that the E-education program has significant effects on unemployment reduction of the graduates. Furthermore, innovation also significantly mediates the association between E-education and reduce unemployment among the students. It implies that the HEI’s should also roll out E-education programs, which would eventually help to reduce unemployment and promote the growth of e-education industry in the country. Finally, policy prescriptions are discussed on the role of an E-education-driven innovation to curtail unemployment in developing countries.